Fast pyrolysis of cellulose, hemicellulose, and lignin : effect of operating temperature on bio-oil yield and composition and insights into the intrinsic pyrolysis chemistry - Ansari, Khursheed Badruddin (2021)
Fast pyrolysis of biomass produces bio-oil as a dominant product. However, the yield and composition of bio-oil are governed by numerous pyrolysis reactions which are difficult to understand because of the multiphase decomposition phenomena with convoluted chemistry and transport effects at millisecond time scales. In this work, thin-film pyrolysis experiments of biopolymers present in the biomass (i.e., cellulose (â¼50 μm), hemicellulose (using xylan as a model biopolymer, â¼12 μm), and lignin (â¼10 μm)) were performed over 200-550 °C, to investigate underlying thermal decomposition reactions, based on the product distribution obtained under reaction-controlled operating conditions. Experimental yields of non-condensable gases, bio-oil, and char at different operating temperatures and in the absence of transport limitations were obtained for each biopolymer. Cellulose- and xylan-derived bio-oil comprised of anhydrosugars, furans, and light oxygenates, in addition to pyrans in cellulosic bio-oil and phenols in xylan-derived bio-oil. Lignin pyrolysis bio-oil contained methoxyphenols, phenolic aldehydes/ketones, low-molecular-weight phenols, and light oxygenates. With an increase in the operating temperature, the anhydrosugars, furans (especially HMF and furfural), and pyrans of cellulosic and xylan bio-oils showed further degradation to form light oxygenates and furanic compounds. In the case of lignin, monolignols, initially formed at lower temperatures, further reacted to form low-molecular-weight phenols and light oxygenates with an increase in the operating temperature. In addition, based on the change in bio-oil yield and composition with temperatures, a reaction network/map was proposed for designing the molecular simulation studies of pyrolysis chemistry and developing detailed and accurate kinetics necessary for the bottom-up design of a pyrolysis reactor.